Beyond the welfare state: the new political economy of welfare - Pierson,Christopher (Cambridge, 2006)
Transforming welfare is now at the top of almost every politician's domes tic agenda. The welfare state, which was once a defining cause for social democrats and, by turns, a source of despair and indifference for those on the right, is now the object of almost universal demands for urgent and profound change. The stakes have been raised, as welfare reform has been transformed into the key strategy for 'reviving the economy' and 'mending the social fabric', but faith in traditional solutions is in seemingly termi nal decline. We are told that, in anything like its traditional form, the welfare state cannot survive. But, as yet, the workable alternatives are quite unclear. Indeed, we now are confronted with a perplexing diversity of pos sible futures all of which somebody promises will resolve our current dif ficulties. What explains this change in the terms of the welfare state debate and where is it headed? How do we pick our way through the abundance of competing explanations? Most importantly, are we really moving, as some suppose, to circumstances that are 'beyond the welfare state? These are the questions addressed in this book. We shall find that the answers are more complex (and the process of reform more difficult) than many contemporary commentators suggest. We shall find, too, that to under stand the newer trajectories of reform we need to know rather more about how we got to be where we are and, indeed, to understand rather more clearly just how and for whom existing welfare states work.
Keywords: Welfare Economics